WARTOŚĆ INFORMACYJNA I FUNKCJE „ZWYKŁEGO CZŁOWIEKA” W TELEWIZYJNYCH WIADOMOŚCIACH - Kołodziej, Jacek Henryk (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This text describes the structural, comparative analysis carried out to reconstruct the role played by ordinary people in TV news anno domini 2015. Main evening news programmes of the three main Polish TV stations were chosen. It was found out quickly that an ordinary man as such does not make any important part neither of narration, nor of the agency of events. If it happens, it always must be balanced by additional, special function. Looking for these functions intersected with the observation that all main structures of news with ordinary people were highly homogenic, organized around the well established factors of media newsworthiness, led to the conclusion that there is relatively small number of such typifications. In its last part the analysis showed that the images and functions of an ordinary man in TV news can be constructed by seven schemes. In all cases they make the types of instrumentalization of what is ordinary – following the golden rule that ‘the mediatized normality must be abnormal’. It its conclusions the text describes every one of these patterns, using the theoretical approach of the gatekeeping, media culture and mediatization theories.